List do Rzymian w Katechezach Cyryla Jerozolimskiego. Sposoby wykorzystania i interpretacji - Widok, Norbert (Vox Patrum, 2018)
Cyril of Jerusalem, the author of the Catechesis delivered to the catechumens and the newly baptized, gave the teachings of Jesus Christ on the basis of the Symbol in force in Jerusalem, and above all on the basis of the Holy Scriptures. He readily referred to the books of the Old and New Testaments, quoting literal citations or paraphrasing individual biblical ideas. Among the frequently quoted biblical books is also the St. Paul’s Epistle to the Romans, which was used by Cyril almost 40 times. Some of Paul’s statements were used as an element of the content link, while others are the starting point for presenting the wider context of Christian teachings to the audience. In most cases, these are literal quotes from the Letter to the Romans. It turns out that the statements of the Apostle of Nations constitute the basis for the interpretation of mainly the Trinitarian aspects of the Christian faith, because individual references serve to bring the listeners closer to the Three Divine Persons. Other quotes Cyril also uses to present some issues of Christian morality.